Segetal flora of some regions of Russia: characteristics of the taxonomic structure - A. S. Tretyakova; O. G. Baranova; N. N. Luneva; T. A. Terekhina; S. M. Yamalov; M. V. Lebedeva; G. R. Khasanova; N. Yu. Grudanov (Труды по прикладной ботанике, генетике и селекции)
The authors’ data on the weed species composition in 8 geographic regions of the Russian Federation were laid at the basis of this survey. The segetal flora comprised weeds of cereals, root crops, and perennial grasses. The composition and taxonomic structure of weed species were analyzed. The total number of weedy plants encompassed 686 plant species. The level of regional weed species diversity was positively related to the area planted. Altai Territory, Udmurtia, and Rostov Province had the greatest weed species diversity, with more than 300 species, while Vologda Province had the lowest diversity (193 species). Most species-rich plant families (Asteraceae Dumort., Poaceae Barnhart, Fabaceae Lindl., Brassicaceae Burnet), genera (Potentila L., Artemisia L., Veronica L., Chenopodium L., Silene L., Trifolium L.), their subsequences, contributions of singlespecies families (17–39%) and genera (57–74%) were relatively stable systematic structure indicators. Only 18% of the species were common for all the regions. In each region there were region-specific groups of species. Weed species compositions in geographically close regions – the European part of Russia and the Urals – showed the greatest similarity. As for geographically distant regions (Altai Territory and Rostov Province), their weedy species compositions were distant and contained large groups of region-specific species.